Allergy-free and easy cooking : 30-minute meals without gluten, wheat, dairy, eggs, soy, peanuts, tree nuts, fish, shellfish, and sesame - Pascal, Cybele (Ten Speed Press, 2012)
""A collection of 75 completely allergen-free recipes that are ready in 30 minutes or less, perfect for parents of kids with food allergies and busy food-allergic professionals who need to get safe food on the table swiftly"--